Pembelajaran Kooperaif Tipe Jigsaw untuk Meningkatkan Ketrampilan Bola Voli dan Bola Basket Siswa SMK - Siswanto, Heri (Media Ilmu Keolahragaan Indonesia, 2013)
The purpose of this study to determine whether cooperative jigsaw type learning to improve volley ball and basket ball skillis class 3 T-3 SMK Negeri 1 Temanggung  in thebsecond semestervof the second semester of the school year 2013/2014. Dalam tests used in data collection techniques to determine student outcomes and techniques nono test in the form of sheets of observation by observatjon to determine the leaning process. The research method used was Classroom Action Research to perform two actions in two cycles. From the results of this research note an improvement in learning outcomes and learning processes. From the initial conditions to an increase in cyclecaverage value of 74 to 79,47 an increase of 7,39 percent. In the two-cycle is the lsst cycle the average value is 85,75Which maens an increase of 15,88 per cent of the initial conditions. Similarly, the learning prosess showed an increase in activity and creativity of studens and teachers. It can be concluded that whether cooperative jgsaw type learning to improve volley ball and basket ball skills class 3 T-3 SMK Negeri 1 Temanggung in the second semester of academic yaer 2013/2014.